Spirocurvulaide, a novel spirobicyclic polyketide from a marine fungus Curvularia sp. IFB-Z10. (February 2019) - An, Fa-Liang; Liu, Wei-He; Zhang, Yi; Tao, Jun; Lu, Yan-Hua
Graphical abstract: Highlights: A novel bicyclic polyketide, spirocurvulaide (1), was produced by Curvularia sp. IFB-Z10. Spirocurvulaide exhibited equal proliferation inhibition against HCC and HCC/5-FU cell lines. A possible biosynthetic pathway of compounds 1 and 2 was described. Abstract: Spirocurvulaide (1 ), a novel bicyclic polyketide with an unprecedented spiro[furan-2, 2′-naphthalene] ring system, was produced by the fungus Curvularia sp. IFB-Z10 in a solid rice medium. Its planar structure and absolute configuration were established based on nuclear magnetic resonance (NMR) data, quantum chemical predictions (QCP) of 13 C NMR chemical shifts and time-dependent density functional theory (TDDFT)/ECD calculations. A plausible biosynthetic pathway of compound1 was also discussed.